Coisa julgada em matéria tributária: limites objetivos e temporais - Munhoz, Flávio de Sá (2020)
This dissertation aims to examine the effects and objective and temporal limits of res judicata in tax matters according to the types of legal relationships. The legal regime of the tax liability relationship will be analyzed in light of the validity of the legal rules, the nature of the tax liability and its classification among the types of legal relationships and the nature and main aspects of the formation of the res judicata in our legal system. We will address the issues related to the appropriateness of a termination action and review action before a res judicata that contradicts the understanding of the Federal Supreme Court and the application of the principles of equality and contributive capacity and the principles of unity and supremacy of the Constitution and of legal certainty as a guarantee of effectiveness as to the past effects of the res judicata